2016
DOI: 10.3354/dao02957
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencephalitis and Listeria monocytogenes, Toxoplasma gondii and Brucella spp. coinfection in a dolphin in Italy

Abstract: Listeria monocytogenes, Toxoplasma gondii and Brucella spp. can infect a wide range of species, including humans. In cetaceans, meningoencephalitis has been associated with T. gondii and Brucella spp. infection, whereas to our knowledge, L. monocytogenes infection has not previously been reported. Meningoencephalitis and L. monocytogenes, T. gondii and Brucella spp. were identified by means of both direct and indirect laboratory techniques in an adult female striped dolphin Stenella coeruleoalba found stranded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…We detected coinfection by marine Brucella and other pathogens, as reported before for several cetacean species infected by Brucella and CeMV (West et al, ), E. tarda (Dawson, Perrett, Young, Davison, & Monies, ), T. gondii (Alba et al, ) or T. gondii and Listeria monocytogenes (Grattarola et al, ). In this study, a stranded female calf Guiana dolphin (case # 8), previously identified as infected by a novel lineage of CeMV (Groch et al, ), was positive for Brucella sp.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We detected coinfection by marine Brucella and other pathogens, as reported before for several cetacean species infected by Brucella and CeMV (West et al, ), E. tarda (Dawson, Perrett, Young, Davison, & Monies, ), T. gondii (Alba et al, ) or T. gondii and Listeria monocytogenes (Grattarola et al, ). In this study, a stranded female calf Guiana dolphin (case # 8), previously identified as infected by a novel lineage of CeMV (Groch et al, ), was positive for Brucella sp.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, the Guiana dolphin (case # 8) and an adult male stranded Clymene dolphin (case # 10), the latter serologically positive, presented CNS findings which diverged from Brucella ‐type lesions as previously described (González et al, ; Hernández‐Mora et al, ; Muñoz et al, ), suggesting potential bacterial infections/coinfections as the cause of the CNS suppurative inflammation (Grattarola et al, ). Complete blood count (CBC) analysis in case # 10 (data not shown) supported an acute bacterial infection.…”
Section: Discussionmentioning
confidence: 75%
“…Special interest has recently been focused on the spillover of pathogens from regional terrestrial animals into the aquatic ecosystem since many typical terrestrial pathogens of zoonotic interest have been found in different classes of marine organisms increasing the reports of lethal cases of infection in marine mammals (Miller et al, 2004;VanWormer et al, 2014;Grattarola et al, 2016;Aguirre et al, 2019;Santoro et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Brucella spp. recovered from sea mammals were first reported in 1994 (Ross et al 1994); since then, several cases of placentitis, abortion, and encephalitis in different marine mammal species (Grattarola et al 2016) have been described (Miller et al 1999;Sierra et al 2014). But marine mammals are also often affected by human activities, including chemical pollution from waste discharge (urban, industrial, and agricultural), acoustic pollution by maritime traffic, vessel collisions, and fishing activities (Arbelo et al 2013;Moore et al 2013).…”
Section: Introductionmentioning
confidence: 99%